(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Actinomycosis is a chronic suppurative infection that is seen anywhere in the body. We report a case of tonsillar hypertrophy for a duration of 1 year in an elderly female patient for whom biopsy and postoperative HPE are sent & results show characteristic sulfur granules and radial spoke-like appearance suggestive of actinomycosis.